The cross-cultural adaptation, validity, and reliability of the Spanish version of the Fremantle Back Awareness Questionnaire - García-Dopico, Nuria; De La Torre-Luque, Alejandro; Wand, Benedict Martin; Velasco-Roldán, Olga; Sitges, Carolina (Frontiers in Psychology, 2023)
Introduction In chronic low back pain (CLBP), disturbed body image has been highlighted as a contributor to the condition and a potential target for treatment. The Fremantle Back Awareness Questionnaire (FreBAQ) allows its assessment. Following international guidelines for the cross-cultural translation of questionnaires, we aimed to translate the FreBAQ into Spanish (FreBAQ-S) and validate the new questionnaire in a sample of Spanish-speaking people with CLBP. Methods Two hundred and sixty-four adults with CLBP (91 males) and 128 healthy controls (34 males) completed an online form including the FreBAQ-S and questionnaires related to the pain experience. All participants were Spanish and no gender identities differing from biological sex were reported. A week later, 113 CLBP participants and 45 healthy controls (41 and 13 males, respectively), re-answered the FreBAQ-S to evaluate test–retest reliability. Confirmatory factor and multigroup analysis assessed the scale consistency on the patient sample. Discriminant and convergent validity were explored by between-group differences and the relationship with clinical characteristics. Reliability relied on Cronbach’s alpha estimates and test–retest (intraclass correlation coefficient, standard error of measurement, minimal detectable change). Results and discussion Confirmatory factor analysis showed a one-factor structure of the questionnaire, without supporting evidence for item deletion (CFI = 0.97; TLI = 0.96; RMSEA = 0.06; SRMR = 0.07; SRMRu = 0.064). Multigroup analyses do not support mean invariance between groups regarding health condition or sex. The FreBAQ-S demonstrated good discriminant and convergent validity, internal consistency (α = 0.82), and test–retest reliability (ICC = 0.78; SE = 3.41; MDC = 5.12). The FreBAQ-S is a valid and reliable tool to assess back awareness in clinical and non-clinical samples.